"Faites un roi, sinon faites la guerre" : l’Action française durant la Grande Guerre (1914-1918) - Audet-Vallée, Kevin (Université de Montréal, 2012)
L’Action française was a significant ideological and intellectual movement in the French Third Republic’s political and cultural history. With its nationalist and antirepublican rhetoric, its flashy political activism and its daily newspaper, it advocated the idea of the restoration of the French monarchy to replace the democratic government, which it considered deleterious. However, it put its royalist agenda on hold during the Great War and refocused on its patriotism. L’Action française backed the governments of the firmly republican Union Sacrée throughout the war and became one of the staunchest allies against the threats to the nation, whether internal or external. At the end of the war, L’Action française had become an acknowledged political actor and had acquired intellectual notoriety. Though significant, this turnaround has nonetheless received little attention in the movement’s historiography. This thesis aims to examine L’Action française’s political journey and ideological evolution based on an analysis of politically-flavored columns published in its daily newspaper between 1914 and 1918 and reports of investigations by the French Department of the Interior (Sûreté générale). This study depicts a rather colorful portrait of the movement’s path and evolution. While L’Action française’s theoreticians and newspaper acquired a great fame thanks to their views and efforts moved by national interest, its political activism was practically destroyed by the military mobilization. Moreover, despite adhering in principle to the political truce brought by the Union Sacrée, it never gave up on its ideological criticism of the republican regime and the promotion of its royalist agenda. Studying the French political scene during the Great War and the role L’Action française reveals this ambiguity while illustrating the singularity of the period’s major debates.
Keywords: Action française; Antiparlementarisme; Charles Maurras; First World War; France; Grande Guerre; Great War; History - European / Histoire - Européenne (UMI : 0335); Léon Daudet; Nationalism; Nationalisme; Première Guerre mondiale; Royalism; Royalisme; Third Republic; Troisième république; Union sacrée